2013
DOI: 10.1080/08120099.2013.787646
|View full text |Cite
|
Sign up to set email alerts
|

Crustal complexity in the Lachlan Orogen revealed from teleseismic receiver functions

Abstract: There is an ongoing debate about the tectonic evolution of southeast Australia, particularly about the causes and nature of its accretion to a much older Precambrian core to the west. Seismic imaging of the crust can provide useful clues to address this issue. Seismic tomography imaging is a powerful tool often employed to map elastic properties of the Earth's lithosphere, but in most cases does not constrain well the depth of discontinuities such as the Mohorovi ci c (Moho). In this study, an alternative imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 47 publications
(83 reference statements)
2
7
0
Order By: Relevance
“…Because of the non-uniqueness of the RF solution (Ammon et al 1990), the NA method combines a Monte Carlo search technique and the properties of the Voronoi geometry in parameter space to find an ensemble of the best-fitting models and performs a global optimization. Fontaine et al (2013b) showed good agreement between Moho depths and results from seismic reflection profiles. Here, we applied the same non-linear inversion method to match the observed radial RFs.…”
Section: Inversion For 1-d Seismic Structure With Six Layerssupporting
confidence: 57%
See 2 more Smart Citations
“…Because of the non-uniqueness of the RF solution (Ammon et al 1990), the NA method combines a Monte Carlo search technique and the properties of the Voronoi geometry in parameter space to find an ensemble of the best-fitting models and performs a global optimization. Fontaine et al (2013b) showed good agreement between Moho depths and results from seismic reflection profiles. Here, we applied the same non-linear inversion method to match the observed radial RFs.…”
Section: Inversion For 1-d Seismic Structure With Six Layerssupporting
confidence: 57%
“…The TAC is inferred to have been connected to the Gawler Craton (Oliver & Fanning 1997;Peucat et al 1999;Fanning et al 2002;Di Vincenzo et al 2007). The Moho depth was estimated in the Gawler Craton at about 40 km by Collins (1991), Clitheroe et al (2000) and between 40 and 45 km by Fontaine et al (2013b). Moreover, all the authors highlight evidences of magmatic underplating beneath the Gawler Craton.…”
Section: Antarctica-australia Lithospheric Connection?mentioning
confidence: 96%
See 1 more Smart Citation
“…However, the goal of this study and particularly with the present limited backazimuthal coverage is not to constrain dipping effect or anisotropic effect on the RFs (e.g. Peng & Humphreys 1997;Savage 1998;Fontaine et al 2013b). Instead, we choose to concentrate on stacking similar radial RFs for a limited range of backazimuths and ray parameters in order to estimate the depths of first-order seismic discontinuities present beneath the station (e.g.…”
Section: R F O B S E Rvat I O N Smentioning
confidence: 99%
“…Earlier RF studies in southeast Australia (Shibutani et al, 1996;Clitheroe et al, 2000;Fontaine et al, 2013a,b) suggested the presence of complex lateral velocity variations in the mid-lower crust that probably reflect the interaction of igneous underplating, associated thinning of the lithosphere, recent hotspot volcanism and uplift. Furthermore, the intermediate to high crustal V p /V s ratio of 1.70-1.78 in this region (Fontaine et al, 2013a), relative to ak135 continental crust where V p /V s is ∼1.68, may indicate a mafic composition that includes mafic granulite rocks, granite-gneiss and biotite gneiss. Body-and surface-wave tomography (Fishwick and Rawlinson, 2012;Rawlinson et al, 2015) reveal P and S wave velocity anomalies in the uppermost mantle beneath Bass Strait and the Lachlan Fold Belt.…”
Section: Introductionmentioning
confidence: 78%